2014
DOI: 10.1155/2014/510157
|View full text |Cite
|
Sign up to set email alerts
|

Coptis chinensis and Myrobalan (Terminalia chebula) Can Synergistically Inhibit Inflammatory Response In Vitro and In Vivo

Abstract: Objectives. To investigate the anti-inflammatory effect of Coptis chinensis plus myrobalan (CM) in vitro and in vivo. Methods. The inflammation in mouse peritoneal macrophages was induced by lipopolysaccharide (LPS). Animal models were established by using ear swelling and paw edema of mouse induced by xylene and formaldehyde, respectively. In vitro, cytotoxicity, the phagocytosis of macrophages, the levels of nitric oxide (NO), induced nitric oxide synthase (iNOS), tumor necrosis factor-α (TNF-α), and interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…CC, which was the plant used in this research work, has also been studied by several other researchers to investigate its medicinal benefits and cosmetics. The anti-inflammatory influence of CC was reported in a research article [ 25 ]. In other research work, the metabolic interaction of some active constituents of CC in human liver microsomes was investigated [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…CC, which was the plant used in this research work, has also been studied by several other researchers to investigate its medicinal benefits and cosmetics. The anti-inflammatory influence of CC was reported in a research article [ 25 ]. In other research work, the metabolic interaction of some active constituents of CC in human liver microsomes was investigated [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coptis chinensis Franch, of the Ranunculaceae family, which is commonly known as Huanglian in China, is one of the 50 fundamental herbs used in traditional Chinese medicine (Li, Tsai, Damu, & Wu, ). Coptidis rhizoma, the dried rhizome of C. chinensis , has commonly been prescribed for various clinical effects, such as anti‐diabetic (Jiang et al, ), hypocholesterolemic and hypoglycemic (Yuan, Tu, Ye, & Wu, ), anti‐inflammatory (Choi et al, ; Cui et al, ), antioxidant (Ban et al, ), analgesia (Tjong et al, ) and neuroprotective (Friedemann et al, ) properties. Coptidis rhizoma is known to harbor a diversity of active isoquinoline‐type alkaloids such as berberine, coptisine, epiberberine, palmatine and jatrorrhizine.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there have been numerous literature reporting several herbs in AGNH exert anti-inflammatory and hepatorenal protective effects. Cui et al demonstrated that Coptidis rhizoma could inhibit the overproduction of inflammatory meditors in macrophages induced by lipopolysaccharide, including induced nitric oxide synthase (iNOS), nitric oxide (NO), tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) ( Cui et al, 2014 ). Furthermore, berberine, the main bioactive ingredient of C. rhizoma , could alleviate cisplatin-induced nephrotoxicity in mice by inhibiting inflammation and oxidative/nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%